2003
DOI: 10.1063/1.1562051
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of heart rate variability via detrended fluctuation analysis and αβ filter

Abstract: Detrended fluctuation analysis (DFA), suitable for the analysis of nonstationary time series, has confirmed the existence of persistent long-range correlations in healthy heart rate variability data. In this paper, we present the incorporation of the alphabeta filter to DFA to determine patterns in the power-law behavior that can be found in these correlations. Well-known simulated scenarios and real data involving normal and pathological circumstances were used to evaluate this process. The results presented … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 33 publications
(91 reference statements)
2
64
0
Order By: Relevance
“…In this way, however, local deviations from the linear trend occurring at specific scales n cannot be detected. The assessment of local deviations may reflect changes in the sympathetic and vagal cardiac control not otherwise visible [7,16], revealing subtle alterations in the overall autonomic regulation of the cardiovascular system [21] and characterizing pathological conditions [6,22]. To evaluate a local slope, that is, as function of n, methods with higher scale resolution are required.…”
Section: Multifractal-multiscale Dfamentioning
confidence: 99%
“…In this way, however, local deviations from the linear trend occurring at specific scales n cannot be detected. The assessment of local deviations may reflect changes in the sympathetic and vagal cardiac control not otherwise visible [7,16], revealing subtle alterations in the overall autonomic regulation of the cardiovascular system [21] and characterizing pathological conditions [6,22]. To evaluate a local slope, that is, as function of n, methods with higher scale resolution are required.…”
Section: Multifractal-multiscale Dfamentioning
confidence: 99%
“…Recent comparative studies have demonstrated that the DFA method outperforms conventional techniques in accurately quantifying correlation properties over a wide range of scales [6,7,8,9,10]. The DFA method has been widely applied to DNA [4,6,7,11,12,13], cardiac dynamics [14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30], human electroencephalographic (EEG) fluctuations [31], human motor activity [32] and gait [33,34,35,36,37], meteorology [38,39], climate temperature fluctuations [40,41,42,43,44,45], river flow and discharge [46,47], electric signals [48,49,50], stellar x-ray binary systems...…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that output signals of many physical [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15], biological [16,17,18,19], physiological [20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35] and economic systems [36,37,38,39,40,41,42,43], where multiple component feedback interactions play a central role, exhibit complex self-similar fluctuations over a broad range of space and/or time scales. These fluctuating signals can be characterized by long-range power-law correlations.…”
Section: Introductionmentioning
confidence: 99%